PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA PEMALSUAN DOKUMEN BERUPA SURAT TANDA NOMOR KENDARAAN (STNK) (Studi Putusan Nomor 241/PID.B/2021 PN Gns) - Reza Sedyadi; Baharudin Baharudin; Anggalana Anggalana (IBLAM Law Review)
Among various types of criminal acts in the community, falsification of letters becomes one of the criminal acts that are rife. For examples criminal cases of falsification of letters are contained in Number: 241/PID.B/2021 PN GNS. Defendant I Suradal and defendant II Efan Efendi committed the criminal act of falsifying documents in the form of STNK. In this study focus on the problem: (1) What are the factors supporting criminal offenders committing STNK counterfeiting crimes? (2) How is the accountability of the perpetrators of STNK counterfeiting? (3) How is the judge’s consideration of the perpetrators of STNK counterfeiting? In this study apply normative juridical approaches as well as empirical juridical. The process of data collection is carried out by field study steps as well as literature studies. The data obtained is then analyzed with qualitative techniques to reach conlcusions in the research conducted. In this study produced answers about what are the factors that cause the perpetrator to commit the crime of forgery, how the perpetrator is responsible and how the judge’s consideration of the perpetrator of the STNK forgery in Number: 241/PID.B/2021 PN GNS.